(untitled) (Journal of Philosophy Culture and Political Science, 2018)
One of the little studied and at the same time actual problems of the philosophy of culture and cultural anthropology is the topic of everyday life. The phenomenon of everyday life has always appeared as a marginal phenomenon that does not represent a social, cognitive value in the sociocultural life of a human being — a theoretical problem. For a number of centuries, for philosophy, the problem of understanding the stable features of sociocultural life, which would impart invariance to sociocultural objects, has become urgent.